2014
DOI: 10.1016/j.foodres.2014.01.031
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pectin concentration and degree of methyl-esterification on the in vitro bioaccessibility of β-carotene-enriched emulsions

Abstract: Soluble fibers, like pectin, are known to influence the physicochemical processes during the digestion of dietary fat and may therefore affect the absorption of lipophilic micronutrients such as carotenoids. The objective of the current work was to investigate whether the pectin concentration and degree of methyl-esterification (DM) influence the bioaccessibility of carotenoids loaded in the oil phase of oil-in-water emulsions. The in vitro β-carotene bioaccessibility was determined for different oil-in-water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 43 publications
1
41
0
1
Order By: Relevance
“…In their study, anionic dietary fibers (pectin) were used, which may have interacted with cationic calcium ions and formed a gel-network that inhibited lipase diffusion or prevented calcium soaps of FFAs being formed. Other studies have suggested that dietary fibers may impact lipid digestion by binding to various components in the GIT, such as calcium ions, bile salts, free fatty acids, and lipase (Palafox-Carlos, Ayala-Zavala, & Gonzalez-Aguilar, 2011;Verrijssen et al, 2014;Qiu, Zhao, Decker, & McClements, 2015). A differential scanning calorimetry study of cellulose ester-bile salt mixtures showed that the bile salts affected the thermal gelation of the cellulose derivatives, which suggested that there was some kind of binding interaction (Torcello-Gόmez & Foster, 2014).…”
Section: Influence Of Methylcellulose On Lipid Digestibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…In their study, anionic dietary fibers (pectin) were used, which may have interacted with cationic calcium ions and formed a gel-network that inhibited lipase diffusion or prevented calcium soaps of FFAs being formed. Other studies have suggested that dietary fibers may impact lipid digestion by binding to various components in the GIT, such as calcium ions, bile salts, free fatty acids, and lipase (Palafox-Carlos, Ayala-Zavala, & Gonzalez-Aguilar, 2011;Verrijssen et al, 2014;Qiu, Zhao, Decker, & McClements, 2015). A differential scanning calorimetry study of cellulose ester-bile salt mixtures showed that the bile salts affected the thermal gelation of the cellulose derivatives, which suggested that there was some kind of binding interaction (Torcello-Gόmez & Foster, 2014).…”
Section: Influence Of Methylcellulose On Lipid Digestibilitymentioning
confidence: 99%
“…Thus, the retardation of lipid digestion observed at high methylcellulose levels may have been partially due to binding of bile salts. Alternatively, it may have been due to the ability of the methylcellulose to increase the viscosity of the aqueous phase around the lipid droplets, thereby slowing down the diffusion of reactants, catalysts, and products involved in the lipid digestion process (Palafox-Carlos et al, 2011;Tokle et al, 2012;Verrijssen et al, 2014).…”
Section: Influence Of Methylcellulose On Lipid Digestibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements were performed at 25 C in a stress-controlled rheometer (MCR 501, Anton Paar, Graz, Austria) using a concentric cylinder geometry (double-wall couette) (Verrijssen et al, 2014). In order to avoid the effect of loading history on the samples, a constant shear rate of 100 s À1 was applied for 60 s, followed by a rest-period of 300 s (shear rate of 0 s À1 ).…”
Section: Viscosity Measurementmentioning
confidence: 99%
“…The integrity of calcium pectinate beads can be reinforced by formation of polyelectrolyte coatings around them, e.g., by electrostatic deposition of cationic biopolymers (such as chitosan) onto the anionic beads[43]. The charge characteristic of pectin can be selected to control lipid digestion and bioactive release, e.g., it has been shown that decreasing DE reduced lipid digestion and bioactive bioavailability[44][45][46].…”
mentioning
confidence: 99%